Cerebral Metabolite Concentrations Are Associated With Cortical and Subcortical Volumes and Cognition in Older Adults - Williamson, John B.; Lamb, Damon G.; Porges, Eric C.; Bottari, Sarah; Woods, Adam J.; Datta, Somnath; Langer, Kailey; Cohen, Ronald A. (Frontiers in Aging Neuroscience, 2021)
Abstract Background: Cerebral metabolites are associated with different physiological processes in brain aging. Cortical and limbic structures play important roles in cognitive aging; however, the relationship between these structures and age remains unclear with respect to physiological underpinnings. Regional differences in metabolite levels may be related to different structural and cognitive changes in aging. Methods: Magnetic resonance imaging (MRI) and spectroscopy (MRS) were obtained from 117 cognitively healthy older adults. Limbic and other key structural volumes were measured. Concentrations of N-acetylaspartate (NAA) and choline-containing compounds (Cho) were measured in frontal and parietal regions. Neuropsychological testing was performed including measures of crystallized and fluid intelligence and memory. Results: NAA in the frontal voxel was associated with limbic and cortical volumes, whereas Cho in parietal cortex was negatively associated with hippocampal and other regional volumes. Hippocampal volume was associated with forgetting, independent of age. Further, parietal Cho and hippocampal volume contributed independent variance to age corrected discrepancy between fluid and crystallized abilities. Conclusions: These findings suggest that physiological changes with age in the frontal and parietal cortices may be linked to structural changes in other connected brain regions. These changes are differentially associated with cognitive performance, suggesting potentially divergent mechanisms.